Molecular evolution of odorant-binding protein genes OS-E and OS-F in Drosophila. - Hekmat-Scafe, D.S.; Dorit, R.L.; Carlson, J.R. (Genetics, 2000)
The Drosophila olfactory genes OS-E and OS-F are members of a family of genes that encode insect odorant-binding proteins (OBPs). OBPs are believed to transport hydrophobic odorants through the aqueous fluid within olfactory sensilla to the underlying receptor proteins. The recent discovery of a large family of olfactory receptor genes in Drosophila raises new questions about the function, diversity, regulation, and evolution of the OBP family. We have investigated the OS-E and OS-F genes in a variety of Drosophila species. These studies highlight potential regions of functional significance in the OS-E and OS-F proteins, which may include a region required for interaction with receptor proteins. Our results suggest that the two genes arose by an ancient gene duplication, and that in some lineages, one or the other gene has been lost. In D. virilis, the OS-F gene shows a different spatial pattern of expression than in D. melanogaster. One of the OS-F introns shows a striking degree of conservation between the two species, and we identify a putative regulatory sequence within this intron. Finally, a phylogenetic analysis places both OS-E and OS-F within a large family of insect OBPs and OBP-like proteins.